Impacts of Marine Heatwaves on Algal Structure and Carbon Sequestration in Conjunction With Ocean Warming and Acidification - Gao, Guang; Zhao, Xin; Jiang, Meijia; Gao, Lin (Frontiers in Marine Science, 2021)
As ocean warms, the frequency, duration, intensity and range of the marine heatwaves (MHWs) are increasing. MHWs are becoming a severe challenge for marine ecosystems. However, our understanding in regard to their impacts on algal structure and carbon sequestration is still deficient or fragmentary, particularly when combined with ocean warming and acidification. In this paper, we reviewed the impacts of MHWs individually and combined with ocean warming and acidification on regime shift in algal community and carbon sequestration of both macroalgae and microalgae. Solid evidence shows that MHWs cause the decline of large canopy macroalgae and increase of turf-forming macroalgae in abundance, leading to the regime shift from kelp forests to seaweed turfs. Furthermore, increased grazing pressure on kelps due to tropicalization facili¬tates the expansion of turfs that prevent the recovery of kelps through plundering light and space. Meanwhile, MHWs could trigger microalgal blooms and the intensity of algal blooms is regulated by severity of MHWs and nutrient availability. MHWs could lead to the decrease of carbon burial and sequestration by canopy-forming macroalgae due to depressed growth and increased mortality. The effects of MHWs on productivity of microalgae are latitude-dependent: positive effects at low and mid latitudes whilst positive effects at high latitudes. Ocean warming and acidification may accelerate the shift from kelps to turfs and thus decrease the carbon sequestration by canopy-forming macroalgae further. We propose that MHWs combined with ocean warming and acidification would reduce the biodiversity and facilitate the thriving of morphologically-simple, ephemeral and opportunistic turfs and diatoms in coastal oceans, and phytoplankton with smaller size in open oceans. This structure shift would not be in favor of long-term carbon sequestration. Future studies could be conducted to test this hypothesis and investigate the impacts of MHWs on carbon sequestration under future ocean conditions.